Media Learning The Introduction of Fruit with Using Technology Augmented Reality - Nur Khafidoh; Muhammad Musthofa Kamal (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
At this time the development of science and technology is growing rapidly, especially information technology. And this research is motivated by the rapid development of technology in the field of education, one of which is AUGMENTED REALITY (AR) technology. This is because the use of Augmented Reality (AR) technology can be implemented as a learning media for the introduction of fruit for kindergarten children, Augmented Reality (AR) is an environment that incorporates 3D virtual objects into the real environment. This is because the use of AR is very interesting and can be developed wider. In this study, Game Engine UNITY was used to build Android-based applications and Visual Studio Code as a text editor to build an application. Accompanied by a book or paper containing a marked image which when directed to the application can display a 3D object visualization. This application can be useful for early childhood, especially at the level of Kindergarten or RA level education in the introduction of fruit. It can be concluded that this application is built capable of displaying 3D object visualization in order to attract students in studying fruits, and the application built is easy to use.